Ageing‐associated increase in SGLT2 disrupts mitochondrial/sarcoplasmic reticulum Ca2+ homeostasis and promotes cardiac dysfunction. Issue 15 (11th July 2020) - Olgar, Yusuf; Tuncay, Erkan; Degirmenci, Sinan; Billur, Deniz; Dhingra, Rimpy; Kirshenbaum, Lorrie; Turan, Belma
Abstract: The prevalence of death from cardiovascular disease is significantly higher in elderly populations; the underlying factors that contribute to the age‐associated decline in cardiac performance are poorly understood. Herein, we identify the involvement of sodium/glucose co‐transporter gene (SGLT2) in disrupted cellular Ca 2+ ‐homeostasis, and mitochondrial dysfunction in age‐associated cardiac dysfunction. In contrast to younger rats (6‐month of age), older rats (24‐month of age) exhibited severe cardiac ultrastructural defects, including deformed, fragmented mitochondria with high electron densities. Cardiomyocytes isolated from aged rats demonstrated increased reactive oxygen species (ROS), loss of mitochondrial membrane potential and altered mitochondrial dynamics, compared with younger controls. Moreover, mitochondrial defects were accompanied by mitochondrial and cytosolic Ca 2+ ([Ca 2+ ]i ) overload, indicative of disrupted cellular Ca 2+ ‐homeostasis. Interestingly, increased [Ca 2+ ]i coincided with decreased phosphorylation of phospholamban (PLB) and contractility. Aged‐cardiomyocytes also displayed high Na + /Ca 2+ ‐exchanger (NCX) activity and blood glucose levels compared with young‐controls. Interestingly, the protein level of SGLT2 was dramatically increased in the aged cardiomyocytes. Moreover, SGLT2 inhibition was sufficient to restore age‐associated defects in [Ca 2+ ]i ‐homeostasis, PLB phosphorylation, NCX activity and mitochondrial Ca 2+ ‐loading. Hence, the present data suggest that deregulated SGLT2 during ageing disrupts mitochondrial function and cardiac contractility through a mechanism that impinges upon [Ca 2+ ]i ‐homeostasis. Our studies support the notion that interventions that modulate SGLT2‐activity can provide benefits in maintaining [Ca 2+ ]i and cardiac function with advanced age.